Platform Web Promosi Bisnis Mahasiswa Terintegrasi Firebase dan WhatsApp - YUSRIDA JELIANTI SIHITE SIHITE; Jatmiko Althaf Aziz; Andika Veriando Saragih; Debi Yandra Niska (LPPM UNIVERSITAS BINA INSAN, 2026)
This study was motivated by the challenges of student business promotion, which is still primarily conducted through social media and WhatsApp groups, making business information difficult to access and poorly organized. This study aims to develop a web-based student business promotion platform integrated with WhatsApp and a popularity-based recommendation system to help users discover the most preferred businesses. The research methods included observation, interviews, and literature review to analyze system requirements, while the system development adopted the Waterfall method consisting of analysis, design, implementation, and testing phases. The system was developed using Node.js, Firebase Realtime Database, and Bootstrap. The main features include user registration, business data management, business search, WhatsApp integration, and a popularity-based recommendation system utilizing user interaction data. The integration of Firebase and WhatsApp enables responsive and real-time data management and communication. System testing was conducted using Black Box Testing and usability testing involving 50 students from Universitas Negeri Medan. The results showed a 100% success rate for all main features, while usability testing achieved an average score of 4.17, categorized as high. The findings indicate that the system effectively supports structured student business promotion, simplifies business information access, and improves communication effectiveness between users and business owners.